The Triaxiality Effect on Damage Evolution in Al-2024 Tensile Samples - Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The effect of triaxiality on the evolution of damage in Al-2024 aluminum cylindrical specimens is studied in this work. Uncoupled and coupled damage models, all of them explicitly dependent on triaxiality, are assessed and compared. These models are characterized by tensile tests on cylindrical specimens without notches, to obtain the material parameters for each model. The capability of each model to predict fracture when different positive triaxial conditions evolve is then evaluated through tensile tests on notched cylindrical specimens. In particular, the damage index, evaluated at the fracture strain level, is compared with the experimental results validating the models. Moreover, the triaxiality evolution in the different specimens is studied in order to assess its effect on damage, demonstrating that the fracture strain decreases at greater triaxiality values. Observations through scanning electron microscopy confirm this pattern; i.e., an increase in triaxiality reveals a shift in the fracture mechanism from a more ductile condition in the original specimens to a more brittle one as the notch radius decreases. In addition, bilinear damage evolution is proposed to describe the physical behavior of the material when the Lemaitre coupled model is considered. In such a case, special attention must be devoted to the material characterization since coupling between hardening material parameters and damage affects the results. © 2024 by the authors.